Defining and Assessing Spirituality and Spiritual Supports: A Rationale for Inclusion in Theory and Practice - Gaventa, William C. (Journal of religion, disability & health, 2001)
The 1992 definition of mental retardation by the AAMR (American Association on Mental Retardation) was the first termination and classification system in developmental disabilities to include the importance of spiritual supports. This paper proposes that “spirituality” be further developed to become the fifth dimension of assessment process. It explores definitions of spirituality, four rationales for enhanced inclusion of spirituality in assessment and supports, and several implications, and some of the challenges which spirituality brings to understandings of professional ethics, identity, and practice.